Unilateral Mandibular Condylar Hyperplasia- a rare entity - Aneel Kumar Vaswani; Bhesham Kumar Shahani; Waseem Mehmood Nizamani; Geeta Aneel; Indra Bhesham (ziauddin University, 2024)
Introduction: True unilateral condylar hyperplasia (CH) of mandible including its variants is an uncommon maxillofacial deformity. It represents unilateral abnormal growth of the mandible including its body and ramus. Discrepancy in the growth of the mandible causing vertical facial asymmetry, creating aesthetic problem resulting in malocclusion as well as psychological issues requiring bi-maxillary surgical correction. In this report we discuss the use of imaging in the diagnosis of these pathologies and investigate its variants. Key Words: Condylar Hyperplasia (CH), Condylar Hyperplasia Variants, Facial Asymmetry.